Reproducibility of Protected Brush Catheter Specimen Cultures in Critically Ill Patients with Suspected Nosocomial Pneumonia - George A Fox; David J Leasa; William J Sibbald; David G McCormack (Canadian Respiratory Journal)
OBJECTIVE: To determine the reproducibility of two protected brush catheter (PBC) specimens obtained during the same bronchoscopy in critically ill patients with suspected ventilator associated pneumonia.